Edukasi Pentingnya Deteksi Dini Kanker Serviks dengan Melakukan Pemeriksaan IVA - Anissa Syafitri Almufaridin; Wulan Dari; Devi Lismasari; Hanif Sukesti; Selvia Susantri; Indah Irasti; Ferti Wahyuni; Marya Amin; Titin Titin; Metty Sylviani; Riska Novianasari (Jurnal Pengabdian Ilmu Kesehatan, 2025)
Cervical cancer is one of the most common types of cancer experienced by women in Indonesia, with incidence rates continuing to rise. Early detection through the IVA (Visual Inspection with Acetic Acid) test is a crucial step in reducing mortality rates from this disease. The aim of this activity was to educate the community about early detection of cervical cancer through IVA testing and to improve participants' knowledge and awareness regarding the importance of routine screening as a preventive measure against cervical cancer. This community service activity was conducted on Tuesday, January 14, 2025, at Buay Nyerupa Public Health Center, involving 20 participants. The activity sought to raise public awareness about the importance of early detection of cervical cancer through the IVA test. The program began with an educational session for participants about early symptoms, risk factors, and the importance of early detection of cervical cancer. Following the educational session, participants underwent IVA testing, conducted directly by healthcare professionals. The evaluation results showed a significant improvement in participants' knowledge. Before the educational session, out of 20 participants, 40% had poor knowledge, 35% had moderate knowledge, and 25% had good knowledge. However, after the educational session, 40% of respondents had moderate knowledge, and 60% had good knowledge. This indicates that after the education, there were no respondents with poor knowledge. It is hoped that this activity will continue to expand its reach and improve reproductive health in the community. Additionally, regular IVA screening can be conducted.